Avaliação de potencial bioisenção de naproxeno sódico e succinato de sumatriptano em comprimidos isolados e em dose fixa combinada - Camila Machado Bretas (2018)
The exemption of pharmacokinetic studies (Biowaiver) has been widely discussed by regulatory agencies worldwide, allowing lower costs in launching generic and similar medications. The biowaiver based on Biopharmaceutics Classification System (BCS) has been highlighting, followed by in vitro in vivo correlation (IVIVC). BCS is based on the solubility and permeability of the drugs and it is divided into four classes. The association of naproxen sodium (NAP) a non-steroidal anti-inflammatory and sumatriptan succinate (SUM) a selective 5-hydroxytryptamine-1 receptor agonist is used for the treatment of migraine attacks. NAP is a class II acidic drug (low solubility and high permeability) and SUM is a class III basic drug (high solubility and low permeability). Studies of solubility, dissolution profiles and cellular permeability were performed (with the isolated and associated drugs) in order to discuss the biowaiver for these drugs. SUM showed high solubility in buffer media with pH 1.2; 4.5; 6.8 and 7.5; dissolution above 85% in 15 minutes (very rapid) and intermediate permeability. Therefore, according to the most current international legislations, SUM may be considered a strong candidate for biowaiver. NAP assays resulted in low solubility in media with pH of 1.2 and 4.5; but high solubility in media with pH at intestinal range (6.8 and 7.5), which suggests good bioavailability in this region. The dissolution of drug products containing NAP was rapid (above 85% in 30 minutes) and the permeability studies confirmed the high absorptive capacity for this drug. NAP could be a biowaiver candidate since it is completely dissolved in the major absorptive region of the gastrointestinal tract, and may be highly absorbed, as evidenced by the pharmacokinetic studies. NAP may also be a candidate for biowaiver by IVIVC, demonstrating good preliminary results. Therefore, with the results of this study, it can be concluded that for the formulations present in the market (with inactive excipients) NAP and SUM may be strong candidates for biowaiver.